SOCIOLINGUISTIC ASPECTS OF THE FUNCTIONING OF THE RUSSIAN LANGUAGE IN UZBEKISTAN: HISTORY AND MODERNITY (American Journal of Research in Humanities and Social Sciences, 2025)
The article examines the sociolinguistic aspect of the Russian language in Uzbekistan, covering its historical development, modern functioning, and influence on interethnic communication. Special attention is paid to its role in educational, scientific, and cultural spheres, as well as its status under the strengthening position of the Uzbek language. The processes of adaptation of the Russian language in a multilingual environment, its perception among various social groups, and prospects for further use are analyzed.